A yellow-green fluorescence quenching-preventing waterborne epoxy coating, and a preparation method and application thereof
By combining CE-Fluo intrinsic fluorescent resin and specific additives, the problems of quenching, low-temperature curing and mechanical properties of fluorescent coatings in high-end protection of 6005 aluminum alloys have been solved, achieving efficient and stable fluorescent marking and protective effects.
Patent Information
- Application Number
- CN202610790487.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-03
- Publication Date
- 2026-08-25
AI Technical Summary
Existing technologies cannot achieve stable anti-quenching fluorescence, low-temperature rapid curing, and high strength and toughness comprehensive performance in high-end protective applications of 6005 aluminum alloy, and cannot meet the needs of industries such as photovoltaics and precision manufacturing.
By using CE-Fluo intrinsic fluorescent resin, covalently bonding NTDI structure fluorescent chromophores, and combining high-purity rutile titanium dioxide, Anquamine® 419 low-temperature curing agent, and BDMA curing accelerator, the resin ratio and additive dosage are optimized to achieve a balance between stable fluorescent properties, low-temperature rapid curing, and mechanical properties of the coating.
It achieves long-term stable fluorescent marking, low-temperature rapid curing, and high strength and toughness of the coating, is compatible with high-end intelligent protection of 6005 aluminum alloy, broadens the construction temperature window, simplifies the construction process, and reduces costs and energy consumption.
Smart Images

Figure CN122628619A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of environmentally friendly functional coatings technology, specifically relating to a yellow-green anti-quenching fluorescent waterborne epoxy coating and its preparation method and application. This coating has intrinsic fluorescence, low-temperature fast curing, high strength and toughness, and excellent anti-corrosion performance. It is especially suitable for photovoltaic frames, precision instrument shells and other components made of 6005 aluminum alloy, and can simultaneously meet the dual stringent requirements of intelligent identification and traceability of industrial products and long-term anti-corrosion protection. Background Technology
[0002] Fluorescent materials, with their unique photoluminescence properties, can absorb light of specific frequencies and emit long-wavelength fluorescence, making them irreplaceable in many cutting-edge fields such as optoelectronic devices, bioimaging, and industrial intelligent traceability. Currently, the mainstream preparation method for fluorescent coatings used in the industrial field to protect metal substrates is physical blending, which involves directly doping commercial organic fluorescent dyes or phosphors into the coating matrix resin. This preparation method is simple, low-cost, and can quickly impart basic fluorescent marking functions to the coating, making it the most widely used technical solution in industrial applications.
[0003] To address the issues of quenching and poor stability in traditional blended fluorescent coatings, numerous improvements have been made to existing technologies. Some research teams employ aggregation-induced emission (AIE) molecular modification techniques to circumvent aggregation quenching by distorting the conformation of fluorescent molecules. Other approaches utilize physical methods such as polymer coating and small-molecule ion-isolated lattice structures to create isolation structures for fluorescent molecules, effectively improving fluorescence stability in laboratory environments. In the field of waterborne epoxy coating modification, existing technologies improve coating toughness by adding reactive diluents such as ethylene glycol diglycidyl ether. Some studies have also attempted to chemically bond fluorescent chromophores to the epoxy resin backbone to enhance fluorescence adhesion stability.
[0004] However, extensive engineering applications have revealed that all existing technical solutions suffer from insurmountable systemic shortcomings, making them unsuitable for high-end protective applications using 6005 aluminum alloy. Firstly, physical blending methods cannot address the core aggregation-induced fluorescence quenching (ACQ) phenomenon. Fluorescent molecules tightly cluster after coating curing, generating strong π-π stacking interactions, leading to non-radiative dissipation of fluorescence energy. Furthermore, the anatase titanium dioxide commonly used in coatings strongly absorbs ultraviolet excitation light, further exacerbating fluorescence quenching, ultimately resulting in low fluorescence brightness, uneven distribution, and rapid decay during use. Secondly, cutting-edge technologies such as AIE molecular modification and polymer encapsulation are only suitable for small-scale laboratory preparation. These processes are cumbersome and require organic solvents, making them incompatible with the environmentally friendly, low-cost, and large-scale production processes of water-based coatings. They also disrupt the continuity of coating film formation, reducing core properties such as coating adhesion and water resistance.
[0005] In addition to the above, existing water-based epoxy coatings for 6005 aluminum alloy also suffer from two inherent technical bottlenecks. First, their low-temperature application performance is poor. At 5°C, the crosslinking reaction rate of conventional water-based epoxy systems decreases significantly, resulting in slow curing or even incomplete film formation, making them prone to powdering and cracking, severely limiting the geographical and seasonal application window for the coatings. Second, there is an inherent contradiction in their mechanical properties. Traditional epoxy coatings generally suffer from the defect of "high hardness inevitably leads to brittleness, and toughening inevitably leads to softness." High-hardness coatings lack sufficient toughness and cannot adapt to the stress generated by thermal expansion and contraction and slight mechanical deformation of aluminum alloys, making them prone to cracking and peeling, thus losing their protective ability. Conversely, high-toughness coatings lack sufficient hardness, resulting in poor wear resistance and impact resistance.
[0006] In summary, the industry currently lacks an integrated coating technology solution that can simultaneously achieve stable anti-quenching fluorescence, low-temperature rapid curing, high strength and toughness mechanical properties, and long-term corrosion protection. This solution cannot meet the intelligent protection needs of high-end industries such as photovoltaics and precision manufacturing for 6005 aluminum alloy components, which is also the problem that this invention urgently needs to solve. Summary of the Invention
[0007] The inventors of this application previously independently developed a CE-Fluo intrinsic fluorescent resin, which has been published as a patent (patent number: CN202610027844.8). This resin breaks through the limitations of traditional physical blending, innovatively fixing the NTDI structure fluorescent chromophore to the epoxy resin main chain and side chain in the form of covalent bonds. It realizes the intrinsic fluorescent properties of the coating at the molecular structure level, completely getting rid of the traditional fluorescent coating preparation mode that relies on the addition of fluorescent powder and fluorescent dye. It avoids the problems of migration and precipitation of small molecule fluorescent substances from the root, and has the inherent advantage of stable luminescence.
[0008] However, during the industrial application of this CE-Fluo intrinsic fluorescent resin to 6005 aluminum alloy protective coatings, the inventors discovered several technical challenges. First, the formulation system lacks compatibility; conventional pigments and additives interfere with intrinsic fluorescence, leading to issues such as fluorescence quenching, brightness decay, and uneven luminescence, thus failing to achieve long-term stable fluorescent marking effects. Second, the resin system exhibits insufficient low-temperature reactivity; the prepared coating cures slowly at 5°C, resulting in poor film integrity and failing to meet industrial requirements for low-temperature application. Third, the mechanical properties of the resin film are uneven; the ratio of rigid structure to flexible segments is not optimized, resulting in coatings that are either insufficiently hard or have poor toughness, making them prone to cracking and peeling due to substrate deformation and external forces, thus exhibiting insufficient protective stability.
[0009] To address the three major technical challenges mentioned above, the inventors conducted extensive systematic experiments and mechanistic studies. Through repeated exploration, they discovered that by precisely selecting pigment systems without fluorescence quenching effects and adapting them to low-interference additive combinations, fluorescence quenching sources within the formulation can be completely eliminated; by combining a low-temperature-specific modified amine curing agent with a highly efficient low-temperature curing accelerator, the low-temperature crosslinking reactivity of the epoxy system can be significantly enhanced, achieving rapid low-temperature curing; and by optimizing the resin ratio, additive dosage, and film-forming process, the ratio of rigidity to flexibility in the coating structure can be precisely controlled, achieving a balanced and unified mechanical property.
[0010] Based on the above research findings, the inventors finally established the overall R&D approach of this application, which is to successfully overcome three major industry pain points—fluorescence quenching, slow low-temperature curing, and easy cracking of coatings—through the formulation and preparation process of coating components A and B. This resulted in the preparation of a water-based epoxy coating that integrates stable anti-quenching fluorescence, fast low-temperature curing, high strength and toughness, and long-term corrosion protection, making it suitable for high-end intelligent protection scenarios of 6005 aluminum alloys, thus completing this invention.
[0011] The specific technical solution is as follows: A yellow-green anti-quenching fluorescent waterborne epoxy coating, consisting of separately stored component A and component B, with a mixing mass ratio of 3~4:1 during construction; By weight, component A comprises: 65.0-75.0 parts of CE-Fluo intrinsic fluorescent resin emulsion, 0.3-0.8 parts of dispersant, 0.2-0.5 parts of defoamer, 0.1-0.3 parts of wetting and leveling agent, 10.0-20.0 parts of rutile titanium dioxide, 0.2-1.0 parts of thickener, and 8-12 parts of deionized water; By weight, component B comprises: 85.0-95.0 parts of water-based epoxy curing agent, 0.5-2.0 parts of dimethyl benzylamine, and 3-5 parts of deionized water; The CE-Fluo intrinsic fluorescent resin emulsion contains intrinsic fluorescent epoxy resin, and the main chain and side chains of the resin molecules are covalently bonded with NTDI fluorescent chromophores.
[0012] Furthermore, the preparation method of the CE-Fluo intrinsic fluorescent resin emulsion includes: (1) Synthesis of fluorescent diol NTDI-Diol: Using 1,4,5,8-naphthalenetetracarboxylic anhydride and ethanolamine as raw materials, the reaction was carried out in anhydrous DMF solvent under nitrogen protection at 120-140℃ for 4-6 hours. After cooling, precipitation, washing and recrystallization, NTDI-Diol was obtained. (2) Synthesis of fluorescent dicarboxylic acid CA-Fluo: Using NTDI-Diol and 4-methylhexahydrophthalic anhydride as raw materials, the reaction was carried out at 40-80℃ for 2-4 hours under the action of a catalyst and nitrogen protection. After precipitation, washing and drying, CA-Fluo was obtained. (3) Synthesis of CE-Fluo waterborne epoxy resin: CA-Fluo is used as a chain extender to carry out a ring-opening addition reaction with bisphenol A type epoxy resin. Lactic acid and succinic anhydride are added as hydrophilic reaction monomers and composite catalysts. After neutralization, the waterborne epoxy resin emulsion is obtained by phase inversion method.
[0013] Further, by weight, component A comprises: 65-70 parts of CE-Fluo intrinsic fluorescent resin emulsion with a solid content of 40-50%, 0.5-0.6 parts of dispersant, 0.3-0.4 parts of defoamer, 0.2-0.3 parts of wetting and leveling agent, 12.0-15.0 parts of rutile titanium dioxide, 0.5-0.8 parts of thickener, and 9.0-11.0 parts of deionized water; By weight, component B comprises: 94-96 parts of water-based epoxy curing agent, 1-2 parts of dimethylbenzylamine, and 3-5 parts of deionized water.
[0014] Furthermore, the dispersant is BYK-190 dispersant or a high molecular weight block copolymer dispersant, the defoamer is BYK-024 defoamer, the wetting and leveling agent is BYK-349 wetting and leveling agent, and the waterborne epoxy curing agent is Anquamine® 419 curing agent.
[0015] Furthermore, the coating has a viscosity of 80-100s at 25℃ using a Forco 4 cup and a VOC content of ≤40g / L; the coating is cured for 40-50h at 5±2℃ and relative humidity ≤65% to obtain a fully dry coating with a pencil hardness of 2H-3H, no cracks in the bending test of a Φ2mm shaft, an elongation at break of 150%-180%, an impact resistance of ≥48kg·cm, and a cross-cut adhesion grade of 0.
[0016] Furthermore, the coating exhibits uniform yellow-green intrinsic fluorescence under light illumination, and its fluorescence intensity does not decrease after being wiped with solvent and immersed in pure water for 168 hours. The corrosion propagation distance of the scratched line in the 500-hour neutral salt spray test is <2.5 mm.
[0017] This invention also protects a method for preparing the yellow-green anti-quenching fluorescent waterborne epoxy coating, comprising the following steps: S1. Preparation of Component A: Under stirring at room temperature, dispersant, defoamer, and wetting and leveling agent are added sequentially to the CE-Fluo intrinsic fluorescent resin emulsion and mixed evenly; then rutile titanium dioxide is added and dispersed evenly. Thickener and deionized water are added, the viscosity of the system is adjusted, and then filtered to obtain Component A. S2. Preparation of component B: Mix the water-based epoxy curing agent, curing accelerator and deionized water according to the ratio, and stir until the system is uniform and transparent without stratification or precipitation to obtain component B. S3. Construction and curing: Mix components A and B in a mass ratio of 3~4:1, mix evenly, and then apply to a 6005 aluminum alloy substrate. Allow to cure naturally in an environment not exceeding room temperature and above 0℃.
[0018] Further, in step S1, after adding rutile titanium dioxide, the mixture is dispersed at high speed of 1200-1500 rpm for 20-30 min until the fineness of the coating is ≤30μm; finally, the speed is reduced to 200-300 rpm, and the pre-dissolved thickener and deionized water are added to adjust the viscosity of the system to 80-100s at a Ford cup of 4 at 25℃. Finally, the mixture is filtered to obtain component A.
[0019] Furthermore, in step S3, the coating is applied to a 6005 aluminum alloy substrate using a spraying or roller coating process, and then naturally cured for 40-50 hours at a temperature of 5±2℃ and relative humidity of ≤65% to obtain the finished protective coating.
[0020] This invention also protects the application of the yellow-green anti-quenching fluorescent waterborne epoxy coating in the protection of 6005 aluminum alloy components. The coating is used for intelligent fluorescent traceability marking or anti-corrosion protection of photovoltaic frames and precision instrument housings.
[0021] Beneficial effects First, this invention utilizes the core technical feature of covalently bonding NTDI fluorescent chromophores to CE-Fluo resin, endowing the coating with stable intrinsic fluorescence properties and completely solving the fluorescence quenching problem of traditional coatings. Traditional fluorescent coatings rely on physical doping of small-molecule fluorescent substances. After the coating cures, the fluorescent molecules freely stack, the intermolecular distance is greatly reduced, and strong π-π planar stacking interactions are generated. The excited state energy is rapidly dissipated through non-radiative pathways, causing severe aggregation-induced fluorescence quenching (ACQ). At the same time, small-molecule fluorescent substances are prone to migration and leakage, and the fluorescence will rapidly decay and eventually disappear after long-term use. In contrast, this invention covalently fixes the fluorescent chromophores to the epoxy resin molecular chain. The spatial position of the fluorescent molecules is firmly fixed and uniformly isolated by the polymer chain segments, fundamentally eliminating the close stacking of fluorescent molecules and completely avoiding the ACQ effect. Meanwhile, the chemically bonded fluorescent structure is integrated with the resin matrix, and there will be no migration or precipitation problems. Combined with the purified non-quenching formulation system, the coating can finally exhibit strong, uniform, and high-contrast yellow-green fluorescence under 365nm ultraviolet light. After repeated wiping with acetone and xylene solvents and immersion in pure water for 168 hours, the fluorescence intensity does not decrease at all. It truly achieves synchronous fluorescence performance and coating service life, far exceeding the stability performance of traditional physically blended fluorescent coatings.
[0022] Secondly, this invention employs a formulation design that replaces conventional anatase titanium dioxide with high-purity rutile titanium dioxide, completely eliminating fluorescence quenching sources within the formulation system and significantly improving fluorescence retention. In existing coating formulations, anatase titanium dioxide is the primary cause of fluorescence quenching. Its unique crystal structure exhibits extremely strong absorption characteristics in the ultraviolet band, absorbing large amounts of 365nm ultraviolet excitation light, preventing fluorescent molecules from obtaining effective excitation energy and interfering with the fluorescence emission process, resulting in a significant decrease in fluorescence intensity. This invention strictly avoids anatase titanium dioxide, selecting rutile titanium dioxide with high coating purity and no ultraviolet absorption impurities. This pigment has extremely weak absorption in the ultraviolet band, does not consume the fluorescence excitation light source, and has high visible light reflectivity, effectively improving fluorescence contrast and visual effect. Testing shows that this optimized formulation method can increase the fluorescence intensity retention rate of the coating by more than 75%, completely solving the fluorescence quenching problem inherent in industrial coating formulation components and ensuring long-term stable and clear visibility of fluorescent markings.
[0023] Furthermore, this invention employs a compound system of Anquamine® 419 low-temperature curing agent and BDMA curing accelerator to achieve rapid low-temperature curing of coatings, completely overcoming the bottleneck of low-temperature application of waterborne epoxy coatings. Conventional waterborne epoxy coatings exhibit extremely high temperature sensitivity in their epoxy-amine crosslinking reaction. At 5°C, the molecular motion rate decreases significantly, the activation energy for the crosslinking reaction is insufficient, and the reaction rate drops sharply. This results in curing times exceeding 72 hours and is prone to problems such as loose film, chalking, and incomplete film formation, severely limiting application in winter and low-temperature regions. The Anquamine® 419 modified amine curing agent used in this invention possesses low-temperature reactivity, adapting to low-temperature crosslinking requirements. Combined with BDMA dimethyl benzylamine accelerator, it significantly reduces the activation energy of the epoxy-amine crosslinking reaction, greatly accelerating the molecular reaction rate at low temperatures. The two components form an excellent synergistic effect. A single curing agent has limited low-temperature reaction efficiency, and a single accelerator has no cross-linking film-forming ability. When the two are combined, they can achieve a synergistic effect of 1+1>2, allowing the coating to be completely dry and form a film within 48 hours in a low temperature environment of 5±2℃ and ≤65% humidity. The film is dense, complete, and defect-free, which greatly expands the application temperature window and regional adaptability of the coating.
[0024] Furthermore, this invention relies on the balanced molecular structure design of CE-Fluo resin to perfectly balance the hardness and toughness of the coating, resolving the inherent contradictions in the mechanical properties of traditional epoxy coatings. Traditional epoxy resin molecular structures are either dominated by rigid benzene ring structures, resulting in high coating hardness but extremely poor toughness, making them prone to brittle cracking under stress; or dominated by flexible segments, resulting in excellent coating toughness but insufficient hardness, wear resistance, and impact resistance, failing to achieve a balance between rigidity and flexibility. In the molecular design stage, the CE-Fluo resin of this invention precisely controls the ratio and connection method of rigid NTDI fluorescent chromophores and flexible polyether segments, achieving an organic fusion of rigid and flexible structures at the molecular level. The rigid structure provides high hardness support for the coating, enabling a pencil hardness of 2H-3H, exhibiting excellent wear resistance and scratch resistance; the flexible polyether segments effectively disperse and buffer external stress and internal stress generated by substrate deformation, improving the coating's ductility. The final coating can pass the bending test of a Φ2mm shaft bar without cracks, and the elongation at break can reach 150%-180%. The impact resistance reaches 50kg·cm, which completely solves the industry problem of traditional coatings being "brittle when hard and soft when flexible", and effectively avoids the problem of coating cracking and protective failure caused by aluminum alloy deformation.
[0025] Finally, this invention achieves multifunctional integration and green construction through an integrated, low-interference, environmentally friendly formulation system, significantly enhancing the industrial application value of coatings. This invention optimizes and selects a low-interference, non-quenching additive system, choosing dispersants, defoamers, and leveling agents with excellent compatibility. This ensures uniform pigment dispersion and a smooth, even paint film without introducing functional groups that can react with fluorescent molecules, thus eliminating fluorescence decay problems caused by additives. Simultaneously, the entire process uses a water-based system with no added organic solvents, resulting in a final coating VOC content ≤40g / L, far below the national mandatory standard limit of GB 38507-2020, making it environmentally friendly and allowing for easy cleaning of application tools. More importantly, this invention can simultaneously achieve three major functions—intelligent fluorescent traceability, long-lasting corrosion protection, and structural reinforcement—with a single coating layer. It replaces the traditional multi-layer coating process of "primer + fluorescent functional layer + topcoat" in the industry, greatly simplifying the construction process, reducing coating costs and energy consumption, and completely avoiding the interlayer adhesion defects of multi-layer coatings. It provides an intelligent protection solution with the same lifespan as the substrate for high-end products such as 6005 aluminum alloy photovoltaic frames and precision instruments.
[0026] In summary, this invention systematically solves multiple technical problems of existing fluorescent epoxy coatings, such as easy quenching of fluorescence, slow low-temperature curing, unbalanced mechanical properties, and single function, from four core dimensions: resin molecule design, formulation system purification, curing system compounding, and mechanical structure regulation. All performance indicators are superior to national standards and industry-standard products, and it has extremely high practicality and commercial promotion value. Attached Figure Description
[0027] To more clearly illustrate the technical solution of the present invention, the accompanying drawings will be briefly described below. Obviously, the drawings described below only relate to some embodiments of the present invention and are not intended to limit the present invention.
[0028] Figure 1 This is a fluorescence effect diagram provided in Embodiment 1 of the present invention. Detailed Implementation
[0029] Preferred embodiments of the present invention will now be described in more detail. While preferred embodiments of the present invention are described below, it should be understood that the invention can be implemented in various forms and should not be limited to the embodiments set forth herein. Where specific techniques or conditions are not specified in the embodiments, they are performed in accordance with techniques or conditions described in the literature in the art or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all commercially available conventional products. In the following embodiments, unless otherwise explicitly stated, "%" refers to weight percentage.
[0030] The following raw materials are used: CE-Fluo resin emulsion: The preparation method is described in patent number CN202610027844.8, specifically including the following steps: S1. Synthesis of NTDI-Diol: In a three-necked flask equipped with a magnetic stirrer and a reflux condenser, 1.0 g (3.73 mmol) of 1,4,5,8-naphthalenetetracarboxylic anhydride (NTDA) and 30 mL of anhydrous DMF were added and stirred to form a suspension. 0.57 g (9.3 mmol) of ethanolamine (molar ratio NTDA:ethanolamine = 1:2.5) was added at once, and the mixture was heated to 130 °C and refluxed for 4 hours under nitrogen protection. After the reaction was completed, the mixture was allowed to cool naturally to room temperature. The reaction solution was poured into excess ice water to precipitate the solid. The crude product was collected by filtration and washed three times each with deionized water and methanol. The product was then purified by recrystallization from DMF to obtain NTDI-Diol with a purity of 98.5%. S2. Synthesis of CA-Fluo: In a dry three-necked flask, add 0.356 g (1 mmol) NTDI-Diol, 0.336 g (2 mmol) 4-methylhexahydrophthalic anhydride (MHHPA), and 2.3 mg p-toluenesulfonic acid (0.65% of the mass of NTDI-Diol). Under nitrogen protection, heat to 80 °C and react for 2 hours. Infrared spectroscopy monitoring revealed the characteristic peak of the hydroxyl group at 3400 cm⁻¹. - ¹) and characteristic peak of acid anhydride (1780 cm⁻¹) - ¹) The peak of the ester group was significantly weakened (1730 cm⁻¹). - ¹) The reaction was significantly enhanced, confirming its completion; after cooling to room temperature, the reactants were dissolved in 10 mL of tetrahydrofuran, poured into 50 mL of ice water to precipitate, filtered to collect the solid, washed three times with methanol, and dried in a vacuum drying oven at 50 °C for 12 hours to obtain CA-Fluo; S3. Synthetic CE-Fluo waterborne epoxy resin: including: S3.1 Initial feeding and dissolution: Add 400.0g of NPEL-128 epoxy resin (epoxy value 0.54eq / 100g) and 100g of propylene glycol monomethyl ether (PM) to a 5L four-necked flask, turn on the mechanical stirrer (300rpm), introduce nitrogen gas, heat to 70℃ and stir for 1 hour to completely dissolve the resin; S3.2 First step of hydrophilization reaction: 29.2g of pure lactic acid (7.3% of the epoxy resin mass) and 5.6g of composite catalyst (DMEA and DMF mixed in a 1:1 molar ratio, 1.0% of the total mass of reactants) were mixed evenly and slowly added dropwise to the reaction system through a constant pressure funnel. The addition was completed in 0.5 hours. The temperature was raised to 95℃ and the reaction was maintained for 2 hours. The acid value was measured and found to be stable at 38mg KOH / g. S3.3 Second step of chain extension and functionalization reaction: Cool to 75℃, add 224.4g CA-Fluo (calculated based on 30% epoxy group consumption) and 44.9g succinic anhydride (20% of the mass of CA-Fluo) at once, keep the reaction at this temperature for 1.5 hours, take a sample and test the acid value to be 50mg KOH / g and the epoxy value to be 0.03eq / 100g; S3.4 Neutralization and Emulsification: Cool to 55℃, slowly add 28g of triethanolamine, stir for 0.5 hours, and check the pH of the system to be 7.8; maintain the stirring speed at 500rpm, slowly add 525g of deionized water, and after 1 hour of addition, the system undergoes a phase inversion (viscosity from 5000mPa). s dropped to 500 mPa (When the system becomes transparent), increase the stirring speed to 1500 rpm and continue dispersing for 20 minutes; S3.5 Post-treatment: Filter through a 200-mesh filter to remove a small amount of mechanical impurities, and obtain CE-Fluo waterborne epoxy resin emulsion (50% solid content).
[0031] Rutile titanium dioxide and anatase titanium dioxide: 99% purity.
[0032] Waterborne epoxy curing agent: Evonik Anquamine® 419 (Germany).
[0033] Table 1 Raw Material Usage Table / Parts by Weight
[0034] Example 1 S1: Preparation of Component A: Under low-speed stirring at room temperature, BYK-190 dispersant, BYK-024 defoamer, and BYK-349 wetting and leveling agent were added sequentially to a 50% solids content CE-Fluo intrinsic fluorescent resin emulsion. Stirring was continued for 5 minutes to ensure complete and uniform mixing of all additives with the resin emulsion. Then, while maintaining stirring, high-purity rutile titanium dioxide was slowly added, and the stirring speed was adjusted to 1200 rpm for high-speed dispersion for 25 minutes. The fineness of the coating was continuously monitored until it was ≤30μm. Finally, the stirring speed was reduced to 300 rpm, and pre-dissolved TEGO ViscoPlus 3010 thickener and deionized water were added. The viscosity of the system was finely adjusted so that the viscosity of the coating stabilized at 90s in a Forco 4 cup at 25℃. After filtration, the mixture was sealed and packaged to obtain the finished product, Component A.
[0035] S2: Preparation of Component B: Accurately weigh Anquamine® 419 waterborne epoxy curing agent, 3055-BDMA dimethyl benzylamine curing accelerator, and deionized water. Mix all raw materials and stir at low speed for 10 minutes until the system is homogeneous and transparent, without layering or precipitation, to obtain the finished product Component B.
[0036] S3: Construction and Curing: Precisely mix the components according to the mass ratio of A:B = 4:1, stir at low speed for 5 minutes to ensure complete fusion of the two components, and apply evenly to the surface of 6005 aluminum alloy substrate using a spraying process. Then place it in a constant temperature and humidity environment with a temperature of 5±2℃ and relative humidity of ≤65% for natural curing for 48 hours to obtain the finished protective coating.
[0037] Figure 1 The accompanying drawings show the fluorescence effect of the coating prepared in Example 1 of this invention under light irradiation. As can be clearly seen from the drawings, the overall surface of the coating is smooth and dense, without cracks, bubbles, pinholes or other defects, and the film quality is excellent. The coating exhibits a uniform, high-brightness yellow-green fluorescence without local unevenness, fluorescence loss, quenching or blackening. This demonstrates the excellent anti-quenching performance and stable intrinsic fluorescence characteristics of the formulation system of this invention, while also reflecting the excellent film integrity and uniformity of the coating.
[0038] Example 2 S1: Preparation of Component A: Under low-speed stirring at room temperature, add BYK-190 dispersant, BYK-024 defoamer, and BYK-349 wetting and leveling agent sequentially to a 50% solids content CE-Fluo intrinsic fluorescent resin emulsion, and stir for 5 minutes to mix evenly. Slowly add high-purity rutile titanium dioxide and disperse at high speed of 1200 rpm for 20 minutes until the coating fineness is ≤30μm. Reduce the speed to 300 rpm, add pre-dissolved TEGO ViscoPlus 3010 thickener and deionized water, adjust the viscosity at 25℃ (Ford Cup 4) to 80s, filter and package to obtain Component A.
[0039] S2: Preparation of component B: Mix Anquamine® 419 waterborne epoxy curing agent, 3055-BDMA curing accelerator, and deionized water, and stir at low speed for 10 minutes until the system is homogeneous to obtain component B.
[0040] S3: Construction and curing: Mix components A and B in a 4:1 mass ratio, stir at low speed until uniform, and then spray onto a 6005 aluminum alloy plate. Curing time is 48 hours at 5±2℃ and relative humidity ≤65% to obtain the finished coating.
[0041] Example 3 S1: Preparation of Component A: Under low-speed stirring at room temperature, add BYK-190 dispersant, BYK-024 defoamer, and BYK-349 wetting and leveling agent sequentially to a 50% solids content CE-Fluo intrinsic fluorescent resin emulsion, and stir for 5 minutes to mix thoroughly. Slowly add high-purity rutile titanium dioxide, increase the speed to 1500 rpm for high-speed dispersion for 30 minutes, ensuring the coating fineness is ≤30μm. Reduce the speed to 300 rpm, add pre-dissolved TEGO ViscoPlus 3010 thickener and deionized water, adjust the 25℃ Ford cup 4 viscosity to 100s, filter and package to obtain Component A.
[0042] S2: Preparation of component B: Mix Anquamine® 419 waterborne epoxy curing agent, 3055-BDMA curing accelerator, and deionized water, and stir at low speed for 10 minutes until homogeneous to obtain component B.
[0043] S3: Construction and curing: Mix components A and B in a 4:1 mass ratio, stir evenly, and spray onto a 6005 aluminum alloy plate. Curing time is 48 hours at 5±2℃ and relative humidity ≤65% to obtain the finished coating.
[0044] Example 4 S1: Preparation of Component A: Under low-speed stirring at room temperature, add a high molecular weight block copolymer dispersant to the CE-Fluo resin emulsion, followed by BYK-024 defoamer and BYK-349 wetting and leveling agent, and stir for 5 minutes to mix evenly. Add rutile titanium dioxide and disperse at high speed of 1200 rpm for 25 minutes until the fineness is ≤30μm. After reducing the speed, add pre-dissolved thickener and deionized water, adjust the viscosity to 90s (25℃), and filter to obtain Component A.
[0045] S2: Preparation of component B: Mix Anquamine® 419 waterborne epoxy curing agent, 3055-BDMA curing accelerator, and deionized water, and stir at low speed for 10 minutes until homogeneous to obtain component B.
[0046] S3: Construction and curing: Mix components A and B in a 4:1 mass ratio, stir evenly, and spray onto a 6005 aluminum alloy plate. Curing time is 48 hours at 5±2℃ and relative humidity ≤65% to obtain the finished coating.
[0047] Example 5 The raw materials, steps, and parameters for preparing component A (S1) and component B (S2) are completely consistent with those in Example 1.
[0048] S3: Construction and curing: Mix components A and B in a 3:1 mass ratio, stir evenly, and spray onto a 6005 aluminum alloy plate. Curing time is 48 hours at 5±2℃ and relative humidity ≤65% to obtain the finished coating.
[0049] Example 6 S1: The raw materials, steps, and parameters for preparing component A are completely consistent with those in Example 1.
[0050] S2: Preparation of component B: Mix Anquamine® 419 waterborne epoxy curing agent, 3055-BDMA curing accelerator, and deionized water, and stir at low speed for 10 minutes until homogeneous to obtain component B.
[0051] S3: Construction and curing: Mix components A and B in a 4:1 mass ratio, stir evenly, and spray onto a 6005 aluminum alloy plate. Curing time is 48 hours at 5±2℃ and relative humidity ≤65% to obtain the finished coating.
[0052] Comparative Example 1 (using anatase titanium dioxide instead of the rutile titanium dioxide of this invention) The difference between this comparative example and Example 1 is that the high-purity rutile titanium dioxide in component A is replaced with anatase titanium dioxide in equal amounts, while the remaining raw material ratios, preparation processes, and construction and curing conditions are exactly the same.
[0053] As shown in Table 2, the comparative example coating exhibits a relative fluorescence value of only 25, weak fluorescence brightness with uneven distribution, and a slightly prolonged drying time at 5℃ to 50 hours, resulting in decreased salt spray resistance. The core reason is that anatase titanium dioxide possesses extremely strong ultraviolet light absorption characteristics, which can consume a large amount of the excitation light source, directly causing severe pigment-type fluorescence quenching and a significant decrease in fluorescence intensity. Simultaneously, trace byproducts generated by ultraviolet absorption slightly interfere with the resin crosslinking reaction, leading to a decrease in film density and a slight reduction in corrosion resistance and curing efficiency. This demonstrates that the use of rutile titanium dioxide in this invention can achieve quenching prevention and protect the fluorescence performance of the film.
[0054] Comparative Example 2 (Physically blended phosphors replacing intrinsic fluorescent resins) The difference between this comparative example and Example 1 is that CE-Fluo intrinsic fluorescent resin is not used; instead, a common non-fluorescent waterborne epoxy resin emulsion (waterborne epoxy resin emulsion 0947A-60W purchased from Guangzhou Weichuang High-Tech Materials Technology Co., Ltd., diluted with water to a solid content of 50%) is used. At the same time, 1.5 parts of traditional yellow-green phosphor (purchased from Thermo Fisher Scientific fluorescent dye, model Alexa Fluor 568) are physically mixed in to introduce fluorescence function. All other conditions are completely the same.
[0055] The initial relative fluorescence value of this comparative example was 60, but the fluorescence distribution was uneven. After solvent wiping, the fluorescence significantly decreased, and it failed to fully cure after more than 72 hours of drying at 5°C. The coating exhibited bending cracks, an elongation at break of only 90%, and blistering failure during salt spray testing. This is because the physically blended small-molecule phosphors lack chemical bonds, leading to severe ACQ aggregation and quenching during curing. Furthermore, the small-molecule phosphors interfere with the epoxy-amine crosslinking reaction, disrupting film continuity. Simultaneously, the poor compatibility between the phosphors and the resin matrix easily forms interface defects, significantly reducing the coating's toughness, adhesion, and corrosion resistance. This indicates that traditional waterborne epoxy resin emulsions, physically blended with phosphors and combined with other components, are difficult to apply to aluminum alloy substrates to obtain products with excellent fluorescence performance.
[0056] Comparative Example 3 (Component B without BDMA low-temperature curing accelerator) The difference between this comparative example and Example 1 is that 3055-BDMA curing accelerator is not added to component B, only the water-based epoxy curing agent and deionized water are retained, and the other conditions are completely the same.
[0057] This comparative example showed a drying time of over 96 hours at 5℃, indicating extremely poor curing efficiency and a slight decrease in impact and salt spray resistance. This is because the low-temperature reactivity of the single Anquamine® 419 curing agent is limited. Without an accelerator, the activation energy of the epoxy-amine crosslinking reaction is too high at low temperatures, resulting in an extremely low molecular reaction rate. Consequently, the paint film cannot fully crosslink and cure over a long period, leading to a loose film with insufficient cohesion. This ultimately results in extremely low application efficiency and a decline in the overall protective performance of the coating, demonstrating the crucial role of curing accelerators in low-temperature curing.
[0058] Comparative Example 4 (Component B does not contain water-based epoxy curing agent, only accelerator and deionized water are retained) The difference between this comparative example and Example 1 is that Anquamine® 419 waterborne epoxy curing agent is not added to component B, and only 1.0 part of 3055-BDMA accelerator and 5.0 parts of deionized water are retained. The other raw material ratios, preparation processes, construction and curing conditions are exactly the same.
[0059] In this comparative example, no effective cross-linking reaction occurred, and a complete paint film could not be formed, resulting in no practical performance. The reason is that the curing accelerator can only catalyze and accelerate the cross-linking reaction; it does not possess the ability to cross-link and form a film on epoxy itself. Without the core curing agent, the resin cannot undergo cross-linking polymerization, and film formation is completely impossible. Combining the test results of Comparative Example 3 (no accelerator, with curing agent, extremely slow curing), Comparative Example 4 (no curing agent, with accelerator, unable to form a film), and Example 1 (the two are combined, perfectly cured in 48 hours), it can be clearly verified that the curing agent provides the basis for cross-linking and film formation, while the accelerator provides low-temperature reactivity. The combination of the two forms a synergistic effect of 1+1>2, and a single component cannot achieve rapid and complete low-temperature curing.
[0060] Performance Test Results and Analysis The samples prepared in the examples and comparative examples were subjected to performance tests, and the specific results are shown in the table below: Table 2 Performance Test Table
[0061] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solution of the present invention, and these simple modifications all fall within the protection scope of the present invention.
[0062] It should also be noted that the various specific technical features described in the above embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the present invention will not describe the various possible combinations separately.
[0063] Furthermore, various different embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention, they should also be regarded as the content disclosed by the present invention.
Claims
1. A yellow-green anti-quenching fluorescent waterborne epoxy coating, characterized in that, It consists of separately stored component A and component B, with a construction mixing mass ratio of 3~4:1; By weight, component A comprises: 65.0-75.0 parts of CE-Fluo intrinsic fluorescent resin emulsion, 0.3-0.8 parts of dispersant, 0.2-0.5 parts of defoamer, 0.1-0.3 parts of wetting and leveling agent, 10.0-20.0 parts of rutile titanium dioxide, 0.2-1.0 parts of thickener, and 8-12 parts of deionized water; By weight, component B comprises: 85.0-95.0 parts of water-based epoxy curing agent, 0.5-2.0 parts of dimethylbenzylamine, and 3-5 parts of deionized water; The CE-Fluo intrinsic fluorescent resin emulsion contains intrinsic fluorescent epoxy resin, and the main chain and side chains of the resin molecules are covalently bonded with NTDI fluorescent chromophores.
2. The yellow-green anti-quenching fluorescent waterborne epoxy coating according to claim 1, characterized in that, The preparation method of the CE-Fluo intrinsic fluorescent resin emulsion includes: (1) Synthesis of fluorescent diol NTDI-Diol: Using 1,4,5,8-naphthalenetetracarboxylic anhydride and ethanolamine as raw materials, the reaction was carried out in anhydrous DMF solvent under nitrogen protection at 120-140℃ for 4-6 hours. After cooling, precipitation, washing and recrystallization, NTDI-Diol was obtained. (2) Synthesis of fluorescent dicarboxylic acid CA-Fluo: Using NTDI-Diol and 4-methylhexahydrophthalic anhydride as raw materials, the reaction was carried out at 40-80℃ for 2-4 hours under the action of a catalyst and nitrogen protection. After precipitation, washing and drying, CA-Fluo was obtained. (3) Synthesis of CE-Fluo waterborne epoxy resin: CA-Fluo is used as a chain extender to carry out a ring-opening addition reaction with bisphenol A type epoxy resin. Lactic acid and succinic anhydride are added as hydrophilic reaction monomers and composite catalysts. After neutralization, the emulsification is carried out by phase inversion to obtain the CE-Fluo intrinsic fluorescent resin emulsion with a solid content of 40~50%.
3. The yellow-green anti-quenching fluorescent waterborne epoxy coating according to claim 2, characterized in that, By weight, component A comprises: 65-70 parts of CE-Fluo intrinsic fluorescent resin emulsion with a solid content of 40-50%, 0.5-0.6 parts of dispersant, 0.3-0.4 parts of defoamer, 0.2-0.3 parts of wetting and leveling agent, 12.0-15.0 parts of rutile titanium dioxide, 0.5-0.8 parts of thickener, and 9.0-11.0 parts of deionized water; By weight, component B comprises: 94-96 parts of water-based epoxy curing agent, 1-2 parts of dimethylbenzylamine, and 3-5 parts of deionized water.
4. The yellow-green anti-quenching fluorescent waterborne epoxy coating according to any one of claims 1-3, characterized in that, The dispersant is BYK-190 dispersant or a high molecular weight block copolymer dispersant; the defoamer is BYK-024 defoamer; the wetting and leveling agent is BYK-349 wetting and leveling agent; and the waterborne epoxy curing agent is Anquamine® 419 curing agent.
5. The yellow-green anti-quenching fluorescent waterborne epoxy coating according to any one of claims 1-3, characterized in that, The coating has a viscosity of 80-100s at 25℃ using a Forco 4 cup and a VOC content of ≤40g / L. The coating is cured for 40-50 hours at 5±2℃ and relative humidity ≤65% to obtain a fully dry coating with a pencil hardness of 2H-3H, no cracks in the bending test of a Φ2mm shaft, an elongation at break of 150%-180%, an impact resistance of ≥48kg·cm, and a cross-cut adhesion grade of 0.
6. The yellow-green anti-quenching fluorescent waterborne epoxy coating according to claim 5, characterized in that, The coating exhibits uniform yellow-green intrinsic fluorescence under light illumination. After being wiped with solvent and immersed in pure water for 168 hours, the fluorescence intensity does not decrease. The corrosion propagation distance in a 500-hour neutral salt spray test is <2.5 mm.
7. A method for preparing the yellow-green anti-quenching fluorescent waterborne epoxy coating according to any one of claims 1-6, characterized in that, Includes the following steps: S1. Preparation of Component A: Under stirring at room temperature, dispersant, defoamer, and wetting and leveling agent are added sequentially to the CE-Fluo intrinsic fluorescent resin emulsion and mixed evenly; then rutile titanium dioxide is added and dispersed evenly. Thickener and deionized water are added, the viscosity of the system is adjusted, and then filtered to obtain Component A. S2. Preparation of component B: Mix the water-based epoxy curing agent, curing accelerator and deionized water according to the ratio, and stir until the system is uniform and transparent without stratification or precipitation to obtain component B. S3. Construction and curing: Mix components A and B in a mass ratio of 3~4:1, mix evenly, and then apply to a 6005 aluminum alloy substrate. Allow to cure naturally in an environment not exceeding room temperature and above 0℃.
8. The preparation method according to claim 7, characterized in that, In step S1, after adding rutile titanium dioxide, disperse it at high speed of 1200-1500 rpm for 20-30 min until the fineness of the coating is ≤30μm; finally, reduce the speed to 200-300 rpm, add the pre-dissolved thickener and deionized water, adjust the viscosity of the system to 80-100s at a Ford cup viscosity at 25℃, and finally filter to obtain component A.
9. The preparation method according to claim 7, characterized in that, In step S3, the coating is applied to a 6005 aluminum alloy substrate using a spraying or roller coating process, and then naturally cured for 40-50 hours at a temperature of 5±2℃ and relative humidity of ≤65% to obtain the finished protective coating.
10. The application of the yellow-green anti-quenching fluorescent waterborne epoxy coating according to any one of claims 1-6 in the protection of 6005 aluminum alloy components, characterized in that, The coating is used for intelligent fluorescent traceability marking or anti-corrosion protection on photovoltaic frames and precision instrument housings.
Citation Information
Patent Citations
Yellow-green fluorescent water-borne epoxy resin for photovoltaic aluminum profile and preparation method of yellow-green fluorescent water-borne epoxy resin
CN121914369A